BIOLOGICALLY ACTIVE COMPOUNDS OF ARTEMISIA ANNUA. ESSENTIAL OIL - D. A. Konovalov; A. A. Khamilonov (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2016)
Artemisia annua is a herblike annual plant which has been used in Chinese folk medicine for more than 2,000 years. In 1970-s sesquiterpenic lactone of artemisinin was isolated from the above-ground part of this plant. Today it is the most efficient known natural and synthetic compound for malaria treatment. The purpose of the study was to review the data from the open sources about a component composition of Artemisia annua essential oil in the spectrum of its pharmacological activity. Methods. The study was carried out using information and searching sources (PubMed, ScholarGoogle), library data bases (eLibrary, Cyberleninca), as well as the results of our studies. Results. We have established that aboveground part of Artemisia annua have a significant amount  of essential oil apart from the sesquiterpene lactones. Essential oil contains more than 120 components, which belong to different classes of natural compounds. The study for dynamics of the essential oil accumulation in the Artemisia annua herb showed that the amount of oil in the herb rises significantly during budding, reaching maximum value in blossom. Qualitative composition and quantitative content of certain components varies depending on ecological and  geographical factors,  plant growing phase, cultivation technology, drying methods etc. Well-known pharmacological studies of essential oil of the Artemisia annua characterize it as a prospective source for the development of new antimicrobial medicinal drugs. Besides, as the studies shown, it can be related to the 6 class according to K. Sidorov's classification - "relatively non-hazardous substances". Conclusion. The analysis of the open sources on the study of essential oil of Artemisia annua made by us, as well as the results of our own studies, including phytochemical studies allow characterizing the essential oil of Artemisia annua as a prospective source for the working out of new antimicrobial drugs.